Implementation of Weighted Product Method for Selection of Math Olympiad Participant - Siti Khairunnisa; Vriska Amanda; Rohan Kristini Purba; Mesran Mesran (Bulletin of Informatics and Data Science, 2023)
So far, the selection of participants for the Mathematics Olympiad still has a number of problems, including a teacher or principal choosing a subject based on eye grades, even though the Science Competition questions that are asked in cities, districts and within the country require other aspects, such as intelligence and experience in Mathematics Competitions. . In addition to the above, sometimes the teacher does not pay attention to all of the above aspects when selecting students, which makes the end result not optimal. In overcoming these problems a system was formed that supports results in the selection of people who will take part in math competitions. In this research, the authors use the Weighted Product method with the results of the research obtained is alternative A5 with a value of 0.2391 as the best alternative